Early experience with day care stapled Haemorrhoidectomy - Shah, Kunda Bikram; Thapa, Bikash Bahadur; Khadka, Santosh; Malla, Srijan; Rawal, Sushil Bahadur; Giri, Naresh Kumar; KC, Nagendra Bahadur; Rai, Sashi (Medical Journal of Shree Birendra Hospital, 2012)
Introducti on: Improvements in anesthesia, pain management, the evolution of minimally invasive surgery and changing attitudes to recovery after surgery have all promoted to the expansion of scope of day care surgery. The use of stapled haemorrhoidectomy is an accepted treatment modality for prolapsing hemorrhoids of varying degree. To evaluate the outcome of patients undergoing stapled hemorrhoidectomy in the early postoperative period with special focus on pain intensity, requirement of analgesic and its feasibility as a day care procedure. Method: Interventional, clinical, hospital based study carried out at Shree Birendra Hospital between November 2010 and May 2011. The feasibility of discharging pati ents on the day of Stapled Hemorrhoidectomy was evaluated. Results: Of the eleven (n=11) patients selected for daycare Stapled Hemorrhoidectomy ten patients ( 90%) could be discharged aft er six hours of observation. Conclusion: Stapled Hemorrhoidectomy is a safe and easily mastered technique with superior results in the immediate/ early postoperative period. The initial cost of the stapling device is the main concern but social and economic savings related to a faster recovery may off set the initial cost especially when it is performed on a day care basis. DOI: http://dx.doi.org/10.3126/mjsbh.v10i2.6456 Medical Journal of Shree Birendra Hospital July-Dec 2011 10(2) 11-14